2011
DOI: 10.3150/10-bej306
|View full text |Cite
|
Sign up to set email alerts
|

On non-stationary threshold autoregressive models

Abstract: In this paper we study the limiting distributions of the least-squares estimators for the non-stationary first-order threshold autoregressive (TAR(1)) model. It is proved that the limiting behaviors of the TAR(1) process are very different from those of the classical unit root model and the explosive AR(1).Comment: Published in at http://dx.doi.org/10.3150/10-BEJ306 the Bernoulli (http://isi.cbs.nl/bernoulli/) by the International Statistical Institute/Bernoulli Society (http://isi.cbs.nl/BS/bshome.htm

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 16 publications
2
9
0
Order By: Relevance
“…In model (5.1), although β 21 = 1, {y t } is not a unit-root process even not a partial unit-root process in Liu et al (2010). √ n( β 21,n − β 21,0 ) is still asymptotically normal.…”
Section: About Here]mentioning
confidence: 99%
“…In model (5.1), although β 21 = 1, {y t } is not a unit-root process even not a partial unit-root process in Liu et al (2010). √ n( β 21,n − β 21,0 ) is still asymptotically normal.…”
Section: About Here]mentioning
confidence: 99%
“…By contrast, the OLS estimator of α 2 is asymptotically consistent with the super n-rate of convergence. In a related paper by Liu, Ling and Shao (2009), the authors have established similar results for α 2 , but have not established any asymptotic theory for α 1 .…”
Section: Introductionmentioning
confidence: 51%
“…This implies that the asymptotic theory for α 2 is the same as that for the unit-root case when µ 2 = ∞ −∞ yI[y ∈ C τ ]π s (dy) = 0, i.e., {y t } has some symmetrical structure in the stationary regime. In this symmetrical case, the asymptotic distribution in (2.15) corresponds to the main result in Theorem 2.1 of Liu, Ling and Shao (2009).…”
Section: Ols Estimation Methods and Asymptotic Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Seo and Linton (2007) proposed a smoothed LSE for the TAR/regression model and showed that the estimated threshold is asymptotically normal with a lower rate of convergence. Liu et al (2011) and Gao et al (2013) studied the LSE for the non-stationary first-order TAR model and Chan et al (2015) adopted the LASSO method to estimate TAR models with multiple thresholds. Gao et al (2017) proposed a non-nested test for TAR models vs.…”
Section: Introductionmentioning
confidence: 99%